ØÙˆÙƒÙ…Ø© Ø§Ù„Ø²ÙƒØ§Ø© ÙÙŠ Ø¶ÙˆØ¡ Ù…Ù‚Ø§ØµØ¯ Ø§Ù„Ø´Ø±ÙŠØ¹Ø© - Rahmatullah Hidri; Zafari, Arsalah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This research discusses zakat governance in the context of sharia maqÄá¹£id, because zakat governance has a special legitimacy purpose that helps Islamic communities in economic problems. The purpose of this study is to clarify the standards of governance control of zakat sharia maqÄá¹£id perspective and to demonstrate the method of zakat governance according to maqÄá¹£id sharia. In this study, researchers used several scientific methods, including: (1) inductive methods to track and collect fiqhiyyah arguments and arguments; (2) descriptive approach, which is the study of the problem of jurisprudence with an accurate description, as well as an explanation of its correlation with various other problems; (3) Analytical methods are methods based on the study of jurisprudic problems in digging, synthesizing and evaluating, and studying their properties and functions in returning elements to their origin. The results showed that the method of zakat governance to achieve sharia maqÄá¹£id is the discipline of members of administrative bodies in collecting and distributing zakat, as well as the supremacy of sharia on the provisions of the berzakat parties, and born from it several important things, among others: transparency, accountability, independence, justice, and social responsibility of zakat management institutions. The criteria that can be used in zakat governance, where governance depends on the extent to which special institutions implement the concepts of governance, namely: the existence of an effective framework basis for the government, the rule of law for all, the capacity of accountability for all private and public institutions in the country (transparency, participation and mechanisms) and the guarantee system of upholding these principles in accordance with the characteristics of each country.